2021
DOI: 10.1021/acs.orglett.1c01117
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Synthesis of α-Aminoamide Utilizing an Umpolung Reaction and Characteristics of α-Hydrazonoester

Abstract: An umpolung reaction with α-hydrazonoesters was investigated, and it was found that α-N,N-dialkylaminoamides could be directly synthesized in yields up to 92% via a concomitant rearrangement of dialkylamino groups. As an application, a short synthesis of an inhibitor of glycine type-1-transporter was accomplished via subsequent functional group transformations in 28% overall yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Herein, we delve into three recent instances that facilitate amide bond formation. Shimizu, Mizota, and their colleagues detailed the rearrangement of α‐hydrazonoesters, yielding α‐aminoamides [234] . Their work revealed that treating hydrazonoesters with Grignard reagents results in rearranged amino tertiary amides.…”
Section: Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we delve into three recent instances that facilitate amide bond formation. Shimizu, Mizota, and their colleagues detailed the rearrangement of α‐hydrazonoesters, yielding α‐aminoamides [234] . Their work revealed that treating hydrazonoesters with Grignard reagents results in rearranged amino tertiary amides.…”
Section: Rearrangementsmentioning
confidence: 99%
“…Shimizu, Mizota, and their colleagues detailed the rearrangement of α-hydrazonoesters, yielding αaminoamides. [234] Their work revealed that treating hydrazonoesters with Grignard reagents results in rearranged amino tertiary amides. The proposed reaction mechanism (Figure 52a) initiates with the organometallic compound adding to the imine nitrogen via a cyclic transition state.…”
Section: Rearrangementsmentioning
confidence: 99%
“…NHC organocatalysis is the most commonly used tool for umpolung chemistry, although other organocatalytic modes, metal catalysis, and photocatalysis are also employed. Alongside these, the stoichiometric use of organophosphine and organometallic reagents has further enriched this chemistry. In this context, depending on the additive present in the reaction medium, organometallic reagents generally react with the carbonyl functionality in either a 1,2 or 1,4 fashion .…”
mentioning
confidence: 99%
“…Later, van Koten introduced the umpolung organozinc addition toward α-iminocarbonyls . However, only a little progress in this reactivity ensued until the great effort of Kozlowski, Shimizu, and Mizota, who contributed significantly and expanded this reactivity for future development . Despite the success achieved in the umpolung reaction of α-imino carbonyls, the umpolung addition to α-diketones remained underexplored (Scheme b).…”
mentioning
confidence: 99%
“…Pioneering work by Kagan overcame this challenge by introducing the umpolung attack of Grignard reagents on nitrogen . Furthermore, umpolung reactivity of dialkylzinc toward α-iminocarbonyls was reported by van Koten et al Over the years Shimizu, Mizota, and Kozlowski have explored this reactivity with great success (Scheme b). , Such reactivity is not restricted only to α-imino esters, as other α-iminocarbonyls have also shown potential efficiency. Few tandem reactivities in the presence of nucleophiles , or electrophiles , have also been reported. However, it is interesting to note that, in contrast to nitrogen umpolung, oxygen umpolung remains underdeveloped.…”
mentioning
confidence: 99%